Fikih Multikultural sebagai Landasan Normatif Dialog Antaragama dalam Masyarakat Plural - Randy R; Adil A; Abdillah Mustari (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Modern society is characterized by the reality of pluralism in ethnicity, culture, language, and religion, which requires social management based on the values of justice and tolerance. In this context, interfaith dialogue becomes an essential instrument for maintaining social harmony, particularly in multicultural countries such as Indonesia. This article aims to examine the concept of multicultural fiqh as a normative foundation for building interfaith dialogue within a plural society. This study employs a qualitative descriptive approach using library research methods, analyzing Qur’anic verses, classical and contemporary tafsir, and scholarly literature related to multiculturalism and interfaith dialogue. The findings indicate that Islam normatively recognizes pluralism as sunnatullah (divine decree), as reflected in the diversity of ethnicities, languages, and religions. Multicultural fiqh, grounded in the framework of maq??id al-shar?‘ah, emphasizes the importance of justice, tolerance (tas?mu?), equality, and respect for human dignity in interreligious relations. The main challenges to interfaith dialogue include social prejudice, religious fanaticism, discrimination, and identity-based conflicts, which can be addressed through the internalization of Qur’anic values and the strengthening of cross-faith communication. Thus, multicultural fiqh plays a strategic role as an ethical and normative framework for enhancing interfaith dialogue and fostering sustainable social harmony in the era of globalization.